Application of RNA-Seq transcriptome analysis: CD151 is an Invasion/Migration target in all stages of epithelial ovarian cancer - Mosig Rebecca A; Lin Li; Senturk Emir; Shah Hardik; Huang Fei; Schlosshauer Peter; Cohen Samantha; Fruscio Robert; Marchini Sergio; D'Incalci Maurizio; Sachidanandam Ravi; Dottino Peter; et al. (BMC, 2012)
Abstract Background RNA-Seq allows a theoretically unbiased analysis of both genome-wide transcription levels and mutation status of a tumor. Using this technique we sought to identify novel candidate therapeutic targets expressed in epithelial ovarian cancer (EOC). Methods Specifically, we sought candidate invasion/migration targets based on expression levels across all tumors, novelty of expression in EOC, and known function. RNA-Seq analysis revealed the high expression of CD151, a transmembrane protein, across all stages of EOC. Expression was confirmed at both the mRNA and protein levels using RT-PCR and immunohistochemical staining, respectively. Results In both EOC tumors and normal ovarian surface epithelial cells we demonstrated CD151 to be localized to the membrane and cell-cell junctions in patient-derived and established EOC cell lines. We next evaluated its role in EOC dissemination using two ovarian cancer-derived cell lines with differential levels of CD151 expression. Targeted antibody-mediated and siRNA inhibition or loss of CD151 in SKOV3 and OVCAR5 cell lines effectively inhibited their migration and invasion. Conclusion Taken together, these findings provide the first proof-of-principle demonstration for a next generation sequencing approach to identifying candidate therapeutic targets and reveal CD151 to play a role in EOC dissemination.